Systematic literature review: correlation of knowledge tuberculosis patients with level adherence in the treatment program - Djembor Sugeng Walujo; Finayatul Jannah (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2022)
Hypertension is a disease due to an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg in patients measured twice with an interval of five minutes in a state of rest or calm. Various types of drugs are used to lower blood pressure, such as diuretics, beta-blocker drugs, ACE-inhibitors, angiotensin II receptor blocking drugs (ARBs), calcium antagonists, and vasodilator drugs. Patient non-compliance in taking hypertension medication is still a problem that needs attention from all health service providers, both doctors, nurses and pharmacists. This article uses a narrative review, in order to identify and summarize previously published articles, avoid duplication of research, and look for new studies that have not been studied. In Ariyani's article (2018), she focuses more on the results of compliance based on the treatment before and after giving the Pill Card Posttest, Pretest. While in Harun's article (2020) it was found that the results of an increase in patient compliance were based on a descriptive analysis of the character of hypertensive patients consisting of gender, age, and age using the Morisky Medication Adherence Scale-8 assessment. Compliance with treatment of hypertensive patients is important because hypertension is a disease that cannot be cured but must always be controlled or controlled so that complications do not occur that can lead to death. Characteristics of age, gender, education, occupation affect medication adherence in hypertensive patients.